Randomized clinical trial to evaluate mental practice in enhancing advanced laparoscopic surgical performance. Issue 1 (21st October 2014) - Louridas, M; Bonrath, E M; Sinclair, D A; Dedy, N J; Grantcharov, T P
Abstract: Background: Mental practice, the cognitive rehearsal of a task without physical movement, is known to enhance performance in sports and music. Investigation of this technique in surgery has been limited to basic operations. The purpose of this study was to develop mental practice scripts, and to assess their effect on advanced laparoscopic skills and surgeon stress levels in a crisis scenario. Methods: Twenty senior surgical trainees were randomized to either conventional training or mental practice groups, the latter being trained by an expert performance psychologist. Participants' skills were assessed while performing a porcine laparoscopic jejunojejunostomy as part of a crisis scenario in a simulated operating room, using the Objective Structured Assessment of Technical Skill (OSATS) and bariatric OSATS (BOSATS) instruments. Objective and subjective stress parameters were measured, as well as non-technical skills using the Non-Technical Skills for Surgeons rating tool. Results: An improvement in OSATS ( P = 0·003) and BOSATS ( P = 0·003) scores was seen in the mental practice group compared with the conventional training group. Seven of ten trainees improved their technical performance during the crisis scenario, whereas four of the ten conventionally trained participants deteriorated. Mental imagery ability improved significantly following mental practice training ( P = 0·011), but not in the conventional group ( P = 0·083). No differences in objective or subjective stress levels or non-technical skills were evident. Conclusion: Mental practice improves technical performance for advanced laparoscopic tasks in the simulated operating room, and allows trainees to maintain or improve their performance despite added stress. Abstract : Improves performance in a simulated situation